Study on the New Method of Finite Element Analysis of Helical Gear Contact - Lu Fengxia; Chen Wenwei; Liu Weiping; Zhu Rupeng; Zou Xiaozhu (Jixie chuandong)
A new method of finite element mesh generation is proposed based on meshing characteristics of helical gear. The contact line in the process of engagement could pass through the unit nodes successively. The flexibility coefficient matrix is obtained by finite element method. Tooth contact analysis（ TCA） model for helical gear is established considering the interaction between participating and non participating meshing point. By introducing boundary and deformation compatibility conditions,the equilibrium equations are established and solved. Finally,the time varying meshing stiffness,tooth surface elastic deformation and load distribution are calculated,moreover compared with the calculated meshing stiffness according to GB/T 3480-1997,the results show that the proposed method is effective.